Using eye-tracking to identify pedestrians' critical visual tasks, Part 1. Dual task approach. (April 2015) - Fotios, S; Uttley, J; Cheal, C; Hara, N
This paper investigates the critical visual tasks of pedestrians, the first step in a review of design guidance for lighting in residential roads. Eye tracking was used to record pedestrians' visual fixations when walking outdoors in daytime and after dark with a concurrent dual task to better understand which fixations were critical. Fixations at critical instances, these being shown by slow reactions to the secondary task, were categorised into one of eight groups. Of these, the path and other people were the most frequent items, with people more likely to be fixated at a far distance and the path at a near distance. After dark the path was more likely to be fixated and other people less likely to be fixated compared with daylight.